Chapter Porti, navi e altri elementi di approdo e commercio lungo l'Arno al tempo di Leonardo: un patrimonio da riscoprire e riattualizzare - Butelli, Elisa (Territori, 2023)
At the time of Leonardo da Vinci, numerous landfalls and transversal passages along the Arno made it easily crossable and navigable in Tuscany, from Valdichiana to the coast. In order to develop a specific knowledge of such elements, and to restore a valuable analytical tile for the recognition of the territorial heritage related to Leonardo's hydraulic design, this chapter presents the work carried out by the authors to map ports, ships, passes and mills along the Arno river course, from Florence to Pisa, also in view of a theoretical reflection on the importance of the water system at Leonardo's time.